Personality dimensions, positive emotions and coping strategies in the caregivers of people living with HIV in Lahore, Pakistan. Issue 4 (11th May 2016) - Ashraf, Mujeeba; Sitwat, Aisha
Abstract : The aim of this research was to study the relationship between personality dimensions, positive emotions and coping mechanisms of caregivers of patients living with HIV. This study used a cross‐sectional research design. A sample comprising 56 caregivers was recruited from HIV/AIDS clinics in three teaching hospitals in Lahore, Pakistan. Data were collected between February and July 2010. Most caregivers were men, and of low socio‐economic status. Individuals with both high and low extraversion used problem‐focused coping, self‐control and accepting responsibility, but those with low extraversion used more escape‐avoidance coping, and they had also high levels of negative emotions. Those high in neuroticism used more tension‐reduction coping than problem‐focused coping, and experienced fewer positive emotions. Regression analysis findings revealed neuroticism as a significant predictor of negative emotions as well as emotion‐focused coping, and only extraversion significantly predicted negative emotions. This research could help in devising psychological management plans for caregivers of patients living with HIV in order to assist them in coping with the burden of care.